Molecular Heterogeneity in Glioblastoma: Potential Clinical Implications - Parker, Nicole Renee; Khong, Peter; Parkinson, Jonathon Fergus; Howell, Viive Maarika; Wheeler, Helen Ruth (Frontiers in Oncology, 2015)
Glioblastomas, (grade 4 astrocytomas), are aggressive primary brain tumors characterized by histopathological heterogeneity. High resolution sequencing technologies have shown that these tumors also feature significant inter-tumoral molecular heterogeneity. Molecular subtyping of these tumors has revealed several predictive and prognostic biomarkers. However, intra-tumoral heterogeneity may undermine the use of single biopsy analysis for determining tumor genotype and has implications for potential targeted therapies. The clinical relevance and theories of tumoral molecular heterogeneity in glioblastoma are discussed.